(untitled) (Quinto Sol, 2024)
Recent historiographical research has posed the question about the “productive dimension of power” and the construction of consensus among the population during the last Argentine civic-military dictatorship (1976-1983). This article extends that question to the Malvinas war, fought between Argentina and Great Britain in 1982. Based on the study of documents declassified in 2015 and kept in the Department of Naval Historical Studies, the article analyzes the social communication and the psychological campaign that the Argentine Navy projected during those days to model celebratory attitudes and feelings towards the Army and to underpin the military operations of the dictatorship in the South Atlantic, and the consequently expected (and frustrated) diplomatic negotiations.